Monolithic Photoassisted Water Splitting Device Using Anodized Ni‐Fe Oxygen Evolution Catalytic Substrate. Issue 19 (23rd May 2017) - Dong, Wan Jae; Song, Young Jin; Yoon, Hansub; Jung, Gwan Ho; Kim, Kisoo; Kim, Sungjoo; Lee, Jong‐Lam
Abstract: Large‐scale industrial application of solar‐driven water splitting has called for the development of oxygen evolution reaction (OER) catalysts that deliver high catalytic activity and stability. Here it is shown that an efficient OER catalytic substrate can be developed by roll‐to‐roll fabrication of electrodeposited Ni‐Fe foils, followed by anodization. An amorphous oxyhydroxide layer directly formed on Ni‐Fe foils exhibits high catalytic activity toward water oxidation in 1m KOH solution, which requires an overpotential of 0.251 V to reach current density of 10 mA cm –2 . The developed catalytic electrode shows the best OER activity among catalysts with film structure. The catalyst also shows prolonged stability at vigorous gas evolution condition for 36 h. To demonstrate the monolithic photoassisted water splitting device, an amorphous silicon solar cell is fabricated on Ni‐Fe catalytic substrate, resulting in lowering OER overpotential under light illumination. This monolithic device is the first demonstration that the OER catalytic substrates and the solar cells are integrated and can be easily applied for industrial scale solar‐driven water electrolysis. Abstract : A Ni‐Fe oxyhydroxide foil is fabricated through continuous roll‐to‐roll compatible methods of electrodeposition and anodization. The catalysts exhibit good oxygen evolution activity and excellent stability. Moreover, Ni‐Fe catalytic substrate is integrated with an amorphous silicon solar cell to demonstrate a monolithic photoassisted water splitting device. This approach provides insights for exploiting highly efficient and industry applicable water splitting device.